2021
DOI: 10.1371/journal.pone.0250803
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and length of stay in older adults with blunt injury in a national multicentre prospective cohort study

Abstract: Background Patients suffering moderate or severe injury after low falls have higher readmission and long-term mortality rates compared to patients injured by high-velocity mechanisms such as motor vehicle accidents. We hypothesize that this is due to higher pre-injury frailty in low-fall patients, and present baseline patient and frailty demographics of a prospective cohort of moderate and severely injured older patients. Our second hypothesis was that frailty was associated with longer length of stay (LOS) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous results from our study of older blunt trauma patients showed that pre-injury baseline frailty was associated with post-discharge functional decline and increased health services utilization [ 9 , 10 ]. Studies on caregivers of patients with dementia have highlighted caregiver burden as a major contributor to post-discharge healthcare utilization [ 11 ].…”
Section: Introductionmentioning
confidence: 97%
“…Previous results from our study of older blunt trauma patients showed that pre-injury baseline frailty was associated with post-discharge functional decline and increased health services utilization [ 9 , 10 ]. Studies on caregivers of patients with dementia have highlighted caregiver burden as a major contributor to post-discharge healthcare utilization [ 11 ].…”
Section: Introductionmentioning
confidence: 97%